Konsep Etika Komunikasi Berdasarkan Perspektif Alquran - Sulaiman RM; Anggra Prayuda; Lahmuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article explores communication theory and communication ethics guidelines from a Quranic perspective. The terms qaulan bligha, qaulan Maisyuro qaulan karima, qaulan ma'rufa, qaulan layyinan, and qaulan sadida are some of the unique terms used in the Quran to explain the principles of communication. Thus, the definition of communication in the Quran can serve as a foundation in building good and polite communication practices in social, political, and other fields. The Quranic guidelines regarding good behavior and communication with both parents, especially when one or both of them are elderly, is one example of how this is done. The expression “karim”, which means “noble” in Arabic, is used in this regard in the Quran. The meaning of the hadith and the Quranic instructions indicate that Muslims have an obligation to uphold the virtues of truth and politeness in discourse, which in the Quran is referred to as qaulan sadidan.